Effect of Different Levels of Aqueous Suspension of Bentonite Nanoparticles on Performance and Carcass Characteristics of Broiler Chickens - Al-Faqieh , Mohammad A.; Abdelqader , Anas; Aburjai, Talal (Jordan Journal of Agricultural Sciences, 2024)
The study aimed to investigate the impact of different concentrations of aqueous suspension of bentonite nanoparticles (ASBN) on the productive performance of broiler chickens. The research was conducted at the University of Jordan poultry farm in Almuwaqar research station. A total of 240 Ross 308 broiler chickens were distributed among four treatments, with three replicates per treatment. Treatment T1 was the control, while T2, T3, and T4 received 1%, 2%, and 3% of ASBN, respectively. The study found that the use of ASBN at levels of 1%, 2%, and 3% significantly (p>0.05) improved the growth performance of broiler chickens. The lowest feed conversion ratio (FCR) was observed in T2 (1% ASBN) on day 28, indicating better feed efficiency. However, carcass characteristics parameters, such as dressing and cut percentages, were not significantly influenced by ASBN treatment. Interestingly, T4 (3% ASBN) resulted in a higher weight of the breast compared to the other treatments. The study concluded that using ASBN at levels of 1%, 2%, and 3% can enhance the growth performance of broiler chickens without negative impacts on their carcass characteristics.